Theory and practice of water and wastewater treatment - Droste, Ronald L. (New York : J. Wiley, 1997)
Droste provides up-to-date coverage of the technologies used in water and wastewater management, including standard practice as well as state of the art. Both theory and design concepts are developed systematically, supported by comprehensive examples
-- Basic chemistry -- The thermodynamic basis for equilibrium -- Acid-base chemistry -- Organic and biochemistry -- Analysis and constituents in water -- Microbiology -- Water, wastes, and disease -- Water components and quality standards -- Water and wastewater treatment operations -- Mass balances and hydraulic flow regimes -- Screening and sedimentation -- Mass transfer and aeration -- Coagulation and flocculation -- Filtration -- Physical-chemical treatment for dissolved constituents -- Disinfection -- Aerobic biological treatment -- Anaerobic wastewater treatment -- Treatment in ponds, land systems, and wetlands -- Sludge processing and land application -- Effluent disposal in natural waters
Includes bibliographical references and index
Keywords: Water -- Purification; Sewage -- Purification; Water Purification